Penyuluhan Akupressur Dismenorea Primer pada Remaja Putri di Puskesmas Bojong II Kabupaten Pekalongan - Eni Trisniningtyas; Naning Dianasari; Mila Cholilah; Kholifah; Endang Kartiasih; Nurmilah; Rini Susanti (Universitas Ngudi Waluyo, 2025)
Adolescence is a dynamic phase of development in a person's life. One of the biological signs of adolescence is the start of menstruation which begins between the ages of 10 and 16 years. Menstruation is a physiological thing that happens to every woman. However, in reality, many women experience menstrual problems, including menstrual pain/ dysmenorrhea. Menstrual pain/ dysmenorrhea is a gynecological complaint due to an imbalance of the hormone progesterone in the blood, resulting in pain. The purpose of this community service is to provide counseling and training on Acupressure to reduce dysmenorrhea pain. This community service activity will be divided into 3 stages of activity, the first is planning, the second is counseling and practicum, and the third is evaluation. Participants in the dysmenorrhea acupressure counseling are adolescent girls. They are the main target because they often experience menstrual pain or dysmenorrhea, which can interfere with daily activities. Acupressure counseling aims to provide knowledge and practical skills about acupressure techniques as an alternative to relieve dysmenorrhea pain. From the results of univariate analysis before counseling was given to 17 respondents, there were 11 respondents who had knowledge in the poor category, after counseling, the results were obtained from 17 respondents, 16 respondents had good knowledge and 1 respondent had knowledge in the poor category. From the results obtained after counseling, there was an increase in respondents' knowledge of the material provided. Abstrak Masa remaja adalah suatu fase perkembangan yang dinamis dalam kehidupan seseorang. Salah satu tanda keremajaan secara biologi yaitu mulainya remaja mengalami menstruasi yang dimulai antara usia 10 sampai 16 tahun. Menstruasi merupakan hal yang bersifat fisiologis yang terjadi pada setiap perempuan. Namun pada kenyataannya banyak perempuan yang mengalami masalah menstruasi, diantaranya nyeri haid/dismenore. Nyeri haid / dismenore adalah keluhan ginekologis akibat ketidakseimbangan hormon progesteron dalam darah sehingga mengakibatkan timbul rasa nyeri. Tujuan pengabdian masyarakat ini adalah untuk memberikan penyuluhan dan pelatihan Akupresur untuk mengurangi nyeri dismenorea. Kegiatan pengabdian masyarakat ini akan dibagi menjadi 3 tahap kegiatan yang pertama perencanaan, kedua penyuluhan dan praktikum yang ketiga evaluasi. Peserta penyuluhan akupresur dismenore adalah remaja putri. Mereka menjadi target utama karena sering mengalami nyeri haid atau dismenorea, yang dapat mengganggu aktivitas sehari-hari. Penyuluhan akupresur bertujuan untuk memberikan pengetahuan dan keterampilan praktis tentang teknik akupresur sebagai alternatif untuk meredakan nyeri dismenore. Dari hasil analisis univariat sebelum diberikan penyuluhan terhadap 17 responden terdapat 11 responden memiliki pengetahuan kategori kurang, sesudah dilakukan penyuluhan didapatkan hasil dari 17 responden sebanyak 16 responden memiliki pengetahuan kategori baik dan 1 responden memiliki pengetahuan kategori kurang. Dari hasil yang didapatkan setelah dilakukan penyuluhan terdapat peningkatan pengetahuan responden terhadap materi yang diberikan.